Smart Branding “Pesona Buaya” in Facilitating Business Identification Number (NIB) Management for MSMEs in Surabaya City - Andhika Akbar Ramadhan; Binti Azizatun Nafi’ah (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
This study aims to analyze the implementation of smart branding by the